The evolution of occupational structures in South Africa 1875-1911 : an analysis of the effects of the resource curse and blessing - Ramela, Omphile Abel (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCom)--Stellenbosch University, 2018.